Preliminary investigation of a multimodal enhanced brain function index among high school and collegiate concussed male and female athletes. Issue 4 (1st October 2020) - Covassin, Tracey; McGowan, Amanda L.; Bretzin, Abigail C.; Anderson, Morgan; Petit, Kyle Michael; Savage, Jennifer L.; Katie, Stephenson L.; Elbin, R. J.; Pontifex, Matthew Brian
ABSTRACT: Objective : The primary purpose of this study was to examine the longitudinal effects of sports-related concussion (SRC) on a multi-faceted assessment battery which included neuropsychological testing, symptom reporting, and enhanced brain function index (eBFI) among athletes with and without SRC. A secondary purpose was to explore longitudinal sex differences among these measures in athletes with and without SRC. Methods : A case-control, repeated-measures design was used for this study. A total of 186 athletes (concussed group: n = 87 controls: n = 99) participated in the study. A repeated-measures design was used in which each athlete was tested at four time points following an SRC: within 72 h of injury (Day 0; 2.0 ± 0.9 days following injury), 5 days following injury (Day 5; 5.0 ± 0.0), at return to play (RTP; 18.3 ± 13.8 days following injury), and within 45 days following RTP (RTP45; 66.2 ± 19.0 days following injury). All analyses were conducted separately using a 2 (Group: concussed, control) × 2 (Sex: male, female) × 4 (Time:Day 0, Day 5, RTP, RTP45) univariate multi-level model including the random intercept for each participant. A higher eBFI score indicates a better performance. Alpha level was set aprior at .05. This study was registered on clinicaltrials.gov (Objective Brain Function Assessment of mTBI/Concussion in College/high school Athletes NCT02477943, NCT02661633, CAS 13–25 NCT03963804). Results : Concussed athletes exhibited impaired eBFI within 72 h of SRC and at Day 5 compared to controls ( p <.001). Analysis of eBFI scores between male and female athletes revealed a main effect of sex ( p =.05), with female athletes exhibiting lower eBFI (33.9 ± 30.7) relative to male athletes (40.4 ± 33.0), however, it did not indicate interactions between sex, group, and time ( p's ≥ 0.786). Conclusion : The eBFI appears to be a useful tool in determining concussed athletes during the acute stages of an SRC. However, this index may lack the sensitivity to detect sex-related differences between groups at various time points during recovery.